Effects of levamisole on the non-specific cellular immune response in grouper, Epinephelus coiodes - Moralba, Marian Argie R. (University of the Philippines in the Visayas, 2003)
The use of immunostimulants in fish culture is very valuable. It enhances the non-specific immune responses of fish hereby increasing their protection against infectious diseases. Levamisole as an immunostimulant could facilitate the function of phagocytic cells and could increase the respiratory burst and bactericidal activities. However, its immunostimulatory effect in grouper, Epinephelusspp has not been investigated. In this study, the immunostimulatory effect of levamisole (Sigma) was determined by injecting its intraperitoneally to groupers, Epinepheluscoioided at different doses (0.5, 5, 10, 20 and 50 mg/kg body weight). After 7 days of injection, formalin-killed Escherichia coli was injected into the swim bladder of the grouper to stimulate phagocyte production. After 4 days, inflammatory swim bladder phagocytes were collected and were examined for their phagocytic, respiratory burst, and bactericidal activities. Phagocytic, respiratory burst and bactericidal activities in grouper treated with levamisole were increased compared with the control group. Furthermore, groupers injected at a dose of 0.5 mg/kg body weight exhibited the most significant (p<0.05) changes in all of the parameters tested. The results of the present study show that levamisole can enhamce the non-specific cellular immune response of grouper. This suggests that the use of levamisole as an immunostimulant can be a potential alternative in minimizing mortalities and increasing culture production of grouper.